Counterclaims in Investment Arbitration : Holding Foreign Investors Accountable for Violations of International Law - Guntrip, Edward, (International Law E-Books Online, Collection 2025., 2024)
Foreign investors benefit from investment protection standards in international investment law which are enforceable in investment arbitration. However, international law does not directly bind foreign investors and investment arbitration strugg